2015
DOI: 10.1177/1759091415605115
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Edema Rapidly Increases Neuronal Excitability Through Activation of NMDA Receptor-Dependent Slow Inward Currents in Juvenile and Adult Hippocampus

Abstract: Cellular edema (cell swelling) is a principal component of numerous brain disorders including ischemia, cortical spreading depression, hyponatremia, and epilepsy. Cellular edema increases seizure-like activity in vitro and in vivo, largely through nonsynaptic mechanisms attributable to reduction of the extracellular space. However, the types of excitability changes occurring in individual neurons during the acute phase of cell volume increase remain unclear. Using whole-cell patch clamp techniques, we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 62 publications
4
71
0
Order By: Relevance
“…In addition to increasing effective concentrations of extracellular ions and neurotransmitters, ECS reductions bring neurons closer together and increase nonsynaptic, neuron-to-neuron electrical field (ephaptic) interactions, resulting in more synchronous firing and bursting activity (Andrew et al 1989; Ballyk et al 1991; Dudek et al 1986). Unsurprisingly, neuronal excitability is highly sensitive to extracellular shifts in osmolarity (Azouz et al 1997; Chebabo et al 1995a; Huang et al 1997; Lauderdale et al 2015), and neurons become more susceptible to seizure in hypoosmolar conditions. Multiple studies have demonstrated that seizures and other epileptiform activity can either be induced by lowering extracellular osmolarity, or abolished by increasing extracellular osmolarity (Dudek et al 1990; Kilb et al 2006; Roper et al 1992; Rosen and Andrew 1990; Saly and Andrew 1993; Traynelis and Dingledine 1989), particularly in regions such as the hippocampal CA1 where the ECS is smaller at baseline (McBain et al 1990).…”
Section: Tissue Swelling and Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to increasing effective concentrations of extracellular ions and neurotransmitters, ECS reductions bring neurons closer together and increase nonsynaptic, neuron-to-neuron electrical field (ephaptic) interactions, resulting in more synchronous firing and bursting activity (Andrew et al 1989; Ballyk et al 1991; Dudek et al 1986). Unsurprisingly, neuronal excitability is highly sensitive to extracellular shifts in osmolarity (Azouz et al 1997; Chebabo et al 1995a; Huang et al 1997; Lauderdale et al 2015), and neurons become more susceptible to seizure in hypoosmolar conditions. Multiple studies have demonstrated that seizures and other epileptiform activity can either be induced by lowering extracellular osmolarity, or abolished by increasing extracellular osmolarity (Dudek et al 1990; Kilb et al 2006; Roper et al 1992; Rosen and Andrew 1990; Saly and Andrew 1993; Traynelis and Dingledine 1989), particularly in regions such as the hippocampal CA1 where the ECS is smaller at baseline (McBain et al 1990).…”
Section: Tissue Swelling and Seizuresmentioning
confidence: 99%
“…In quiescent conditions, astrocytes are thought to maintain the so-called “ambient glutamate” concentration in the extracellular space, possibly through release by VRAC or a related channel (Cavelier and Attwell 2005; Le Meur et al 2007). In hypoosmolar conditions, NMDA receptor-dependent slow inward currents (SICs) have also been observed in hippocampal CA1 neurons even when neuronal firing is blocked and vesicles depleted of neurotransmitter (Fiacco et al 2007; Lauderdale et al 2015), suggesting volume-dependent glutamate release from a nonsynaptic source. Astrocytic glutamate released by a Ca 2+ -dependent process has also been reported to induce SICs.…”
Section: Vrac and Volume Regulationmentioning
confidence: 99%
“…Cellular swelling, noted as a prominent feature in CSD, increases EA. It is thought that the expansion of the intracellular space leads to generation of a slow inward current and the generation of action potentials through NMDA receptors [50]. Following induction of spreading depression, enhanced NMDA, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA), and kainate receptor-binding sites were noted in rat hippocampus, which may lower the threshold for EA [51].…”
Section: Csd and Epilepsymentioning
confidence: 99%
“…It is a known phenomenon that hyponatremia can cause brain edema, thus causing neurologic and psychiatric manifestations, and even death. Edema can lead to impaired function in cells by reducing the extracellular space and activating NMDA receptors and calcium channels (5). In our case, we think that hyponatremia due to polydipsia led to transient hippocampal dysfunction and that the symptoms improved with the correction of sodium levels.…”
mentioning
confidence: 68%
“…Animal studies have shown that hyponatremia causes hippocampal neurotransmitter changes, and thus cortically spreading depression and epilepsy (4,5). To our knowledge, our case is the first to be associated with hyponatremia.…”
mentioning
confidence: 83%